The Economics of Mileage Restrictions for Railway Workers in Western Canada - Simpson, Wayne; Peters, Frank (Relations industrielles / Industrial Relations, 1983)
The purpose of this paper is to examine the economics of the mileage payment System, to understand the problems created for the union and C.P.R. management and to examine potential solutions to the problem.